Estudo experimental para uso de sistema híbrido de energia renovável com células fotovoltaicas orgânicas em processo de eletrorrecuperação de zinco - Rodrigo Alberto Moreira Gomes (2021)
This work evaluated the use of a customized hybrid renewable energy system (HRES) with organic photovoltaic (OPV) cells for producing a high-purity metal by electrowinning. This process usually represents the most energy intensive one in the mining industry. A key advantage on the use of the developed system is that the electric charge is inherently generated as direct current (DC), which can be directly supplied to the electrowinning cells without using intermédiate rectifiers. This approach eliminates the energy losses associated, thus increasing the overall efficiency of the power system, and also decreases the carbon footprint of the industrial facility. In this context, the main purpose of this first work was to evaluate the energy saving performance of the technology and its application to produce a quality product, which was characterized by morphology, crystal structure and bending behavior. The electrowinning of zinc was selected as case study. Thus, zinc electrodeposition tests were conducted under conditions typically practiced in industrial operations. The results demonstrated the proper functioning of the HRES system, since constant DC current was supplied to the process. On particular days with global horizontal irradiances in the range from 100 W/m2 to 1200 W/m2, 26±4% of the total current injected in the electrowinning cell was generated by the used OPV cells. In Brazil, this performance corresponds to carbon mitigation of about 6.4x10-2 t of carbon dioxide equivalents (CO2eq) per t of zinc produced. The use of this system also allowed the production of zinc cathodes with morphology and structure typically described in literature and found in industry, which were ductile enough to allow bending without fracturing. These findings indicate that hybrid systems with photovoltaic cells represent an alternative to save energy and increase the sustainability of electrowinning processes.